Terephthalate, a plastic monomer, triggers phosphate metabolism rewiring in yeast - Sarah Takallou; Ryan Lancaster; Sebastian Kinshin; Thomas David Daniel Kazmirchuk; Ashkan Golshani; Eugene Fletcher (Proceedings of the National Academy of Sciences, 2026)
Plastic pollution poses an escalating global threat, demanding biological strategies capable of transforming waste into valuable products. Polyethylene terephthalate (PET) can be hydrolyzed into its monomers, including terephthalate, but microbial valorization of these monomers is constrained by their intrinsic toxicity. Here, we define the cellular basis of terephthalate toxicity in Saccharomyces cerevisiae by integrating genome-wide chemogenomic profiling, transcriptome, and physiological analyses. We identified an association of phosphate-dependent enzymes involved in threonine biosynthesis and glucose metabolism with yeast survival in terephthalate. Our data demonstrate that terephthalate reprograms phosphate metabolism, triggering a noncanonical activation of the phosphate regulon. This response is characterized by strong induction of the high-affinity Na + /phosphate symporter PHO89 and simultaneous repression of Pho4-dependent acid phosphatases. This rewiring elevates phosphate uptake 2.21 ± 0.14-fold, consistent with increased intracellular phosphate availability that supports phosphorylation-dependent control of glucose metabolism. Genetic perturbation experiments showed that PHO89 overexpression in a pho4Δ background enhanced yeast tolerance to 0.3 M terephthalate in a context-specific manner and that this pathway is specific to terephthalate toxicity under the conditions tested. Together, these findings reveal previously unexplored biological basis of terephthalate toxicity, showing that it alters phosphate signaling and the phosphorylation networks that depend on it. This mechanistic insight provides a foundation for engineering industrial yeast strains capable of converting hydrolyzed PET into value-added chemicals, and for enabling sustainable biosynthesis of terephthalate from renewable feedstocks.